2008
DOI: 10.1155/2009/410272
|View full text |Cite
|
Sign up to set email alerts
|

Euler‐Euler Large Eddy Simulation of a Square Cross‐Sectional Bubble Column Using the Neptune_CFD Code

Abstract: In this work, we report on Euler-Euler large eddy simulation (EELES) of dispersed bubbly flow in a square cross-sectional bubble column. Simulations are performed using the Neptune_CFD package, and results processed using the SALOME platform. The motivation to undertake this study is to check our implementation of the Smagorinsky subgrid-scale (SGS) model into Neptune_CFD. We outline all the physical models used, and we present instantaneous realizations of velocity and void fraction fields in order to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…This model incorporates the influence of the gas bubbles in the turbulence by means of additional source terms in the SGS equation and is taken to be proportional to the product of the drag force and the slip velocity between the two phases. This approach was used in work of Niceno et al [10] through the use of a one-equation model. They found significant influence of the additional source terms as used by Pfleger et al [43], as shown in Figure 2.…”
Section: Effect Of Bubble-induced Turbulence (Bit)mentioning
confidence: 99%
See 4 more Smart Citations
“…This model incorporates the influence of the gas bubbles in the turbulence by means of additional source terms in the SGS equation and is taken to be proportional to the product of the drag force and the slip velocity between the two phases. This approach was used in work of Niceno et al [10] through the use of a one-equation model. They found significant influence of the additional source terms as used by Pfleger et al [43], as shown in Figure 2.…”
Section: Effect Of Bubble-induced Turbulence (Bit)mentioning
confidence: 99%
“…[10]. Niceno et al [10] investigated LES with E-E approach for a gas-liquid flow in a square crosssectional bubble column. They demonstrated the applicability of a one-equation model for the SGS kinetic energy ( SGS ).…”
Section: Dhotre Et Almentioning
confidence: 99%
See 3 more Smart Citations